Arabidopsis MSI1 functions in photoperiodic flowering time control - Steinbach, Yvonne (Frontiers Media S.A., 2014)
Appropriate timing of flowering is crucial for crop yield and the reproductive success of plants. Flowering can be induced by a number of molecular pathways that respond to internal and external signals such as photoperiod, vernalization or light quality, ambient temperature and biotic as well as abiotic stresses. The key florigenic signal FLOWERING LOCUS T (FT) is regulated by several flowering activators, such as CONSTANS (CO), and repressors, such as FLOWERING LOCUS C (FLC). Chromatin modifications are essential for regulated gene expression, which often involves the well conserved MULTICOPY SUPRESSOR OF IRA 1 (MSI1)-like protein family. MSI1-like proteins are ubiquitous partners of various complexes, such as POLYCOMB REPRESSIVE COMPLEX2 or CHROMATIN ASSEMBLY FACTOR 1. In Arabidopsis, one of the functions of MSI1 is to control the switch to flowering. Arabidopsis MSI1 is needed for the correct expression of the floral integrator gene SUPPRESSOR OF CO 1 (SOC1). Here, we show that the histone-binding protein MSI1 acts in the photoperiod pathway to regulate normal expression of CO in long day (LD) photoperiods. Reduced expression of CO in msi1-mutants leads to failure of FT and SOC1 activation and to delayed flowering. MSI1 is needed for normal sensitivity of Arabidopsis to photoperiod, because msi1-mutants responded less than wild type to an intermittent LD treatment of plants grown in short days. Finally, genetic analysis demonstrated that MSI1 acts upstream of the CO-FT pathway to enable an efficient photoperiodic response and to induce flowering.